Estratégias organizacionais e competências gerenciais: estudo em instituições de ensino superior do setor privado - Magalhães, Noeme Milfont (2009)
Based on the management competences concepts and the relations with the strategies, this research has as the main goal, to verify, up to perception from directors of private higher education institutions located in Fortaleza, Ce, if there is relation between management competences and structure strategies. With this aim, we started to check the strategies used by private higher institutions, the management competences, according to the directors, are essential to this activity, as well as the importance level that, in directors‟ point of view studied in this research, are essential in strategies execution. The development of this research was possible by using the Methodology Strategies based on four-pole method developed by De Bruyne, Herman and Schoutheete (1977), having four components, epistemological pole, theory pole, morphologic pole and technical pole. The research was made by a preliminary data finding, using exploratory and depiction way. The methodologies was made by using qualitative and quantify methods collected using forms filled in by 8 private higher education institution‟s managers in Fortaleza,Ce. The first form had four steps; the first step had as the main intention to know the director‟s profile, the second one wanted to check the Institution‟s strategies, the third step verified the core competences and the management competences, and the last step had the intention to realize if the Higher Institutions explain clearly the competences asked to the directors; the second form was built based in information collected in first form like strategies and management competences, and wished to measure, up to perception from directors, the importance of each competence to execute the strategies. After finishing the research, noticed as one result that institutions pre-define strategies in a participative way. The other result achieved is that the directors, even not officially, are conscious about the competences required in their function. And the last result was the fact that, in director‟s perception, there is a higher importance level when using management competences in order to execute the strategies, what let us think that there is a relation between them.